KEUNGGULAN STRATEGI BERSAING UKM DI SULAWESI TENGAH - Farid Farid (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
To analyze cost leadership variables, differentiation, and focus simultaneously and significantly against the benefits of SMEs. To analyze the most dominant variant variation variables affect the competitive advantage of SMEs. Together, the three factors or variables that become the research analysis of Cost Leadership, Diferensiasi, and Focus, have a significant and significant influence on the Competitive Advantage of SMEs. Separately or farsial, that the variables that become the research analysis of the variable Leadership Cost, Diferensiasi, and Focus, have a significant or significant influence on Competitive Advantages SMEs. And Of the three factors, the most dominant factor of influence is the Differentiation factor of 2.829.